A scoping review of the literature on grandparents of children with disabilities. Issue 13 (19th June 2022) - Novak-Pavlic, Monika; Abdel Malek, Sandra; Rosenbaum, Peter; Macedo, Luciana G.; Di Rezze, Briano
Abstract: Purpose: The objectives of this review were to: (a) explore the extent and nature of available research on non-custodial grandparents of children with physical, intellectual, or neurodevelopmental disabilities and (b) descriptively summarize the research findings from those studies. Methods: We followed the five-stage scoping review methodology to identify relevant studies from four databases: Medline, CINAHL, Embase, and PsycINFO. Primary, peer-reviewed studies that explored grandparent-related topics in the context of childhood disability were included. Results: Thirty-one studies were identified and analyzed. All of the studies followed non-experimental and qualitative study designs. In the last decade, there has been a growing interest in research on this population ( n  = 15). Grandparents varied considerably in age, education, employment status, and living arrangements ( n  = 4680). Grandmothers represented the vast majority of the population (82%). We grouped the grandparent-related findings from the individual reports into four categories: 1. Adjustment to grandchild's disability, 2. Roles, 3. Perceptions, and 4. Experiences. Conclusion: Grandparents of children with disabilities are a heterogeneous population that experiences unique challenges in their grandparenting role. Future studies on this topic should be oriented toward high-quality, experimental study designs that take into consideration cultural, religious and demographic factors. Grandparents' involvement in healthcare should be encouraged. IMPLICATIONS FOR REHABILITATION: Grandparents of children with developmental disabilities who are not primary caregivers to their grandchild(ren) are significant family members in many families. They face unique challenges in adapting to their grandchild's disability and interacting with professionals regarding their grandchild's disability and functioning. Although there is considerable heterogeneity within this population, most grandparents share the experiences of gradual emotional adjustment to their grandchild's disability, active family involvement, positive perceptions of their family and grandchild's disability and lack of services for them. There are no identified interventions in the research literature that aimed to support grandparents of children with disabilities.